2003
DOI: 10.1093/humrep/deg329
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a levonorgestrel-releasing intrauterine system on angiogenic growth factors in the endometrium

Abstract: These results provide the first evidence that more than one angiogenic factor could be implicated in aberrant endometrial angiogenesis resulting in breakthrough bleeding in LNG-IUS acceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
3
19
0
Order By: Relevance
“…In addition to the proliferation of endometrial glands and stroma, EGF, and EGF-R may also be involved in the control of endometrial angiogenesis during the menstrual cycle (10). Clinical evidence suggests that the expression of angiogenic factors in the endometrial vessels increases under strong progestin stimulation, as observed in levonorgestrel intrauterine system users (24), and this concept may be expanded to EGF-R as suggested by the present study. Thus, EGF-R is a candidate mediator of progestin action in more than one target within the differentiating endometrium.…”
Section: Discussionsupporting
confidence: 59%
“…In addition to the proliferation of endometrial glands and stroma, EGF, and EGF-R may also be involved in the control of endometrial angiogenesis during the menstrual cycle (10). Clinical evidence suggests that the expression of angiogenic factors in the endometrial vessels increases under strong progestin stimulation, as observed in levonorgestrel intrauterine system users (24), and this concept may be expanded to EGF-R as suggested by the present study. Thus, EGF-R is a candidate mediator of progestin action in more than one target within the differentiating endometrium.…”
Section: Discussionsupporting
confidence: 59%
“…The LNG-IUS has been shown to cause an increase in VEGF levels in the endometrium at 3 and 6 months time points [50]. Importantly, this study demonstrated a positive correlation between changes in VEGF levels and clinically reported irregular bleeding, a correlation rarely shown in other studies.…”
Section: Progestogen Effects On Angiogenic Factorssupporting
confidence: 61%
“…Progesterone has been strongly linked with the production of basic fibroblastic growth factor (bFGF) in non-neuronal tissues such as the ovaries and uterus [15]. Furthermore, a norgestrelonly intrauterine release system significantly increases plasma and endometrial bFGF level [16]. In our recent publication, we observed norgestrel-mediated induction of bFGF, a neurotrophic factor repeatedly associated with protection from lightinduced photoreceptor degeneration, in the retina.…”
Section: Progestogens As Modulators Of Neuronal Survivalmentioning
confidence: 86%